2015
DOI: 10.1038/srep08003
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation of cholera toxin B subunit in Nicotiana benthamiana: impacts on host stress response, production yield and vaccine potential

Abstract: Plant-based transient overexpression systems enable rapid and scalable production of subunit vaccines. Previously, we have shown that cholera toxin B subunit (CTB), an oral cholera vaccine antigen, is N-glycosylated upon expression in transgenic Nicotiana benthamiana. Here, we found that overexpression of aglycosylated CTB by agroinfiltration of a tobamoviral vector causes massive tissue necrosis and poor accumulation unless retained in the endoplasmic reticulum (ER). However, the re-introduction of N-glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 63 publications
(117 reference statements)
4
73
0
1
Order By: Relevance
“…Alternatively, in plant expression systems, CTB is expressed in whole plants grown in controlled growth rooms or greenhouses. Previously, our lab has produced recombinant CTB in tobacco plants (Nicotiana benthamiana) using a plant virus vector overexpression system (CTB-KDEL; plant-made CTB; Table 1), with the aim to economically mass-produce the vaccine antigen to facilitate global cholera vaccination [41][42][43]. CTB-KDEL was generated as a result of this endeavor; we genetically modified CTB to add an ER retention signal to the C-terminus, which was critical to mitigate ER stress/tissue necrosis upon overexpression and achieve high-level accumulation in leaf tissue [41,42].…”
Section: Cholera Toxinmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, in plant expression systems, CTB is expressed in whole plants grown in controlled growth rooms or greenhouses. Previously, our lab has produced recombinant CTB in tobacco plants (Nicotiana benthamiana) using a plant virus vector overexpression system (CTB-KDEL; plant-made CTB; Table 1), with the aim to economically mass-produce the vaccine antigen to facilitate global cholera vaccination [41][42][43]. CTB-KDEL was generated as a result of this endeavor; we genetically modified CTB to add an ER retention signal to the C-terminus, which was critical to mitigate ER stress/tissue necrosis upon overexpression and achieve high-level accumulation in leaf tissue [41,42].…”
Section: Cholera Toxinmentioning
confidence: 99%
“…Previously, our lab has produced recombinant CTB in tobacco plants (Nicotiana benthamiana) using a plant virus vector overexpression system (CTB-KDEL; plant-made CTB; Table 1), with the aim to economically mass-produce the vaccine antigen to facilitate global cholera vaccination [41][42][43]. CTB-KDEL was generated as a result of this endeavor; we genetically modified CTB to add an ER retention signal to the C-terminus, which was critical to mitigate ER stress/tissue necrosis upon overexpression and achieve high-level accumulation in leaf tissue [41,42]. Our analyses demonstrated that CTB-KDEL is virtually identical to original CTB in regards to GM1-ganglioside binding affinity, molecular stability and vaccine efficacy to induce anti-toxin IgG and IgA antibodies upon oral immunization in mice [41].…”
Section: Cholera Toxinmentioning
confidence: 99%
See 3 more Smart Citations